Analysis of Financial Literacy, Financial Technology, and Lifestyle on Financial Behavior of Generation Z in Pulo Village - Azhima, Zoya Azrin; Pinem, Dahlia (Formosa Journal of Sustainable Research, 2024)
This research is included in quantitative research to find out the influence of financial literacy, financial technology, and lifestyle on the financial behavior of Generation Z in Pulo Village. Generation Z in Pulo Village was chosen as the object in this research with a total population of 547 Generation Z. The sampling technique in this research used probability sampling and the sample selection in this research used simple random sampling. A total of 180 students were selected from all RWs. Data collection was carried out by distributing questionnaires via Google Forms and analyzed using Partial Least Square (PLS). This research obtained the results of (1) financial literacy has a positive effect on the financial behavior of Generation Z in Pulo Village, (2) financial technology has a positive effect on the financial behavior of Generation Z in Pulo Village, (3) lifestyle has a positive effect on financial behavior of Generation Z in Pulo Village